Effects of combining two lactic acid bacteria as a starter culture on model kimchi fermentation. (October 2020) - Lee, Jae-Jun; Choi, Yun-Jeong; Lee, Min Jung; Park, Sung Jin; Oh, Su Jin; Yun, Ye-Rang; Min, Sung Gi; Seo, Hye-Young; Park, Sung-Hee; Lee, Mi-Ai
Graphical abstract: Highlights: Combined effects of different mixing ratios of starter cultures were investigated. Volatile and non-volatile compounds were different depending on the ratio of LAB. Discrimination of properties of kimchi was explained by microbial communities. PCA showed clear differences in metabolites according to LAB starter culture. Abstract: This study aimed to establish a mixed starter culture to standardize the flavor of kimchi, a traditional Korean food. Leuconostoc mesenteroides and Lactobacillus sakei were selected for the culture based on their key roles in kimchi fermentation. The effects of various starter culture mixing ratios on the overall fermentation process were investigated. Fermentation was carried out at 15 °C for 72 h. In the microbial community analysis, a similar ratio to the initial mixed inoculated ratio was observed in the microbial environments. Treatment with high-rate L. mesenteroides inoculation, exhibiting hetero-fermentative characteristics, led to the production of mannitol (1393.11 mg/100 g), acetic acid (57.70 mg/kg), and lactic acid (1141.90 mg/kg), in addition to the induction of a rapid increase in the number of viable cells, thereby reducing the pH (pH 3.9). Conversely, treatment with high-rate L. sakei inoculation, exhibiting homo-fermentative characteristics, led to the production of less mannitol and acetic acid, with more lactic acid. Principal component analysis score plots showed a distinct difference in kimchi metabolites depending on the lactic acid bacteria (LAB) starter culture. Therefore, by using mixed LAB starter strains, this study demonstrated the value of various characteristics and standardized manufacturing of kimchi. LAB types and inoculation ratios greatly affected the types and concentration of metabolites in kimchi fermentation.